Effect of graphene oxide flakes size and number of layers on photocatalytic hydrogen production - Ewelina Gacka (Nature Portfolio, 2021)
Abstract The present study explored the correlation between the photocatalytic activity toward hydrogen production of the graphene-based materials and graphene oxide (GO) morphology. In this work we applied the technique based on the combination of time-dependent sonication and iterative centrifugation cascades, which were designed to achieve nanosheets size and the number of layers selection. First such obtained GO dispersions were characterized by atomic force microscopy (AFM), scanning electron microscopy (SEM) and optical spectroscopy. Those combined measurements showed that the intensity of the π-π peak at 230 nm seems to be very sensitive to the number of layers of nanosheets. Next, GO dispersions were used to establish influence of the size and the number of layers of GO flakes on the photocatalytic hydrogen production in the photocatalytic system, containing eosin Y as a sensitizer, triethanolamine as a sacrificial electron donor, and CoSO4 as precatalyst. The H2 production efficiency varied by a factor of 3.7 for GO dispersions sonicated for various amount of time. Interestingly it was found that too long ultrasound treatment had negative impact on the GO enhancement of hydrogen production which was related to the fragmentation of GO flakes. The photocatalytic system produced the highest amount of H2 when graphene oxide occurs as monolayers and efficiency becomes lower with the decrease of GO sheets size. Our results demonstrate the importance of optimizing the size and the number of layers of the GO flakes prior to preparation of GO-based materials.